PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TGT (TEAMS GAMES TOURNAMENTS)DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA PADA SISWA KELAS IV SD NEGERI 04 PADANG GANTING - HASMEGAWATI HASMEGAWATI (JURNAL MANAJEMEN PENDIDIKAN, 2019)
This study aims to improve the learning outcomes of fourth grade students at SD Negeri 04 Padang Ganting in Mathematics with the subject of integer count operations, Smallest Multiples Alliances (KPK) and Scattered Fellowship Factors using the TGT Cooperative Learning Model. This research is a collaborative classroom action research. The subjects in this study were grade IV students at SD Negeri 04 Padang Ganting with a total of 18 students. This research took place in two cycles. Cycle 1 consists of 4 meetings and cycle 2 consists of 2 meetings. Data collection techniques in this study are observation and objective tests. The instrument used was the observation sheet and objective test questions. The data analysis technique used is descriptive quantitative and descriptive qualitative. Indicators of success are determined if if the class average increases from pre-action, cycle I and cycle II. The results showed that student mathematics learning outcomes have increased. This is indicated by an increase in the grade average value, which is when the pre-action 6.8 increases to 7.22 in the first cycle of meeting I, in the second meeting increased to 7.38 then increased again in the second cycle of meetings I7, 55 and in the second cycle the second meeting became 8.0. Besides that, from the observation data obtained before the students were given action, they were seen to be less active in learning activities, learning activities were more dominated by teachers. After being given action students look active both during the question and answer activity and during group activities.